2017
DOI: 10.1371/journal.pone.0178136
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from problems in adolescent family relationships to midlife mental health via early adulthood disadvantages – a 26-year longitudinal study

Abstract: Poor childhood family conditions have a long-term effect on adult mental health, but the mechanisms behind this association are unclear. Our aim was to study the pathways from problematic family relationships in adolescence to midlife psychological distress via disadvantages in early adulthood. Participants of a Finnish cohort study at the age of 16 years old in 1983 were followed up at ages 22, 32 and 42 years old (N = 1334). Problems in family relationships were measured with poor relationship with mother an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 70 publications
3
18
0
1
Order By: Relevance
“…To the best of our knowledge, however, the link between poor family relations and premature death has not been shown in earlier research. Yet, our findings are in line with previous studies showing that poor family relations were associated with adult somatic and mental health problems [6,7,8,9,10]. Such health problems are, in turn, related to an increased risk of mortality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To the best of our knowledge, however, the link between poor family relations and premature death has not been shown in earlier research. Yet, our findings are in line with previous studies showing that poor family relations were associated with adult somatic and mental health problems [6,7,8,9,10]. Such health problems are, in turn, related to an increased risk of mortality.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, in their analyses of two British cohorts, Morgan et al [7] found that poor parent-child relationships predicted mental health problems in adulthood. Using data from a Finnish cohort study, Berg et al [8] showed that problems in adolescent family relationships were associated with psychological distress in mid-adulthood. Poor family relationships may however also affect somatic health in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…A mediating factor for this association was family connectedness and support [42]. In contrast, poor family relationships in adolescence predicted mental ill-health later in life [43]. Social support together with internal resources were also positively correlated with mental health in a cross-sectional study among university students, while perceived stress showed a negative association with mental health [44].…”
Section: Introductionmentioning
confidence: 99%
“…Family is the smallest social miniature in a community which comprises of adults, adolescents and children with each responsible of the well-being of the other (Kurniawan, 2015;Tutwiler, 2017). Its problems are quite worrisome to the community (Afdal, 2015;Berg, Kiviruusu, Karvonen, Rahkonen, & Huurre, 2017;Tseng & Hsu, 2018). The most rife phenomenon is the discovery of cases of violence (Herzberger, 2019;Roberson & Wallace, 2016), carried out against wives (women) and their children (Anjani, 2016;Borneo, 2016;Merung, 2016;Rasool, 2016;Utama Hs, 2017).…”
Section: Introductionmentioning
confidence: 99%